Assessing benefits of computer-based video training and tools on learning outcomes and motivation in mechanical engineering education: digitalized intervention and approach - Resendiz-Calderón, César D.; Farfan-Cabrera, Leonardo I.; Cazares-Ramírez, Irving O.; Nájera-García, Pedro; Okoye, Kingsley (Frontiers in Education, 2024)
Traditionally, laboratory work has been a common approach to facilitate the acquisition of practical skills and familiarize the undergraduate students, particularly engineering students, with specialized tools and equipment. However, the conventional in-person labs often experience challenges such as limited resources and space, instructor availability, and inflexible schedules. The emergence of digital tools and the recent COVID-19 pandemic have prompted educators to reconsider their teaching methods. To this effect, this paper introduces an innovative approach and teaching methodology to address the challenges in traditional engineering education within the laboratory. It presents a methodology that combines cost-effective instructional videos and portable kits to promote autonomous development of practical skills in undergraduate engineering students. The proposed teaching methodology was grounded on the Descriptive Decision theory and Learning-Oriented Assessment (LOA), which are theoretical framework and type of students’ learning outcome (SLO) model that studies the rationality behind the decisions that the users are disposed to make, as well as level of outcome of the students’ learning process or performance. Motivation among the students was assessed using the Model of Academic Motivation Inventory (MUSIC Inventory) to evaluate the impact of the proposed teaching method and learning intervention on the interest of the students. The method was implemented in four independent courses at two different campuses of Tecnologico de Monterrey. The results show that the proposed learning approach was effective in helping students develop hard skills with reduced instructor intervention. Moreover, high levels of motivation was reported through the MUSIC methodology and test administered to the participating students at the end of the courses. The outcome of this study can be used to inform and support the curriculum design by the educators, promote effective policy and decision making by the university leaders, and encourage wide adoption of the digitalized-education.